A Bispecific Antifibrin-antiplatelet Urokinase Conjugate (BAAUC) Induces Enhanced Clot Lysis and Inhibits Platelet Aggregation - Ruef, Johannes; Nordt, Thomas K.; Peter, Karlheinz; Runge, Marschall S.; Kübler, Wolfgang; Bode, Christoph (Thrombosis and Haemostasis, 1999)
Thrombolysis is well established in the treatment of acute myocardial infarction. However, clinical application of thrombolytic agents has limitations with respect to efficacy and specificity. To achieve highly effective and at the same time clot-selective plasminogen activation urokinase was coupled to a bispecific antibody consisting of the mono-valent Fab’ from the antifibrin monoclonal antibody 59D8 and the monovalent Fab’ from the anti-glycoprotein GPIIb/IIIa monoclonal antibody 7E3. The bispecific antifibrin-antiplatelet urokinase conjugate (BAAUC) was synthesized and characterized. Assays with either immobilized platelets, GPIIb/IIIa or fibrin showed an increase in plasminogen activation compared to uncoupled urokinase by 10-fold, 58-fold and 13-fold, respectivley (p < 0.0001 each). In vitro clot lysis was performed on platelet-rich and fibrin-rich clots and revealed an up to 5-fold higher potency of BAAUC compared to uncoupled urokinase (p < 0.0001). In vitro platelet aggregation was effectively inhibited by the hybrid molecule, whereas urokinase had no effect. BAAUC and two monospecific urokinase-conjugates, UK-59D8-IgG and UK-7E3-(Fab’)2 were compared with each other with regard to similar tests. In vitro clot assays with platelet-rich and platelet-poor clots were performed. BAAUC achieved a significantly higher plasminogen activation compared to each of the monospecific conjugates (p < 0.05, respectively). We conclude that BAAUC, a bispecific plasminogen activator with antifibrin and antiplatelet properties has the potency to lyse both fibrin-rich and platelet-rich thrombi with high efficacy and to effectively inhibit platelet aggregation.